CDL: Creating value through sustainability - HWANG, Soo Chiat (Institutional Knowledge at Singapore Management University, 2016)
City Developments Limited (CDL) has been publishing an annual dedicated sustainability report, in line with the Global Reporting Initiative’s reporting guidelines, since 2008. In January 2016, Esther An, chief sustainability officer at CDL, produced the 2015 sustainability report using an integrated reporting approach. She saw the fundamental challenge of integrated reporting as communicating to stakeholders the business and financial impact of the firm’s efforts in Environmental, Social and Governance (ESG) integration. The business environment was also changing as consumers demanded more transparency and regulators required more non-financial disclosure from companies. Leaving external pressures aside, CDL had always taken pride in being a socially responsible company. For over two decades, CDL had embraced sustainability in its corporate philosophy and business strategy. This focus is evident in the management of its operations both as a developer and landlord, and also through its building designs and construction methods. Adhering to the integrated reporting approach will allow a more holistic form of reporting that linked the impact of the firm’s social and environmental performance to its financial bottom line. Through the analysis of this case, students will learn about the challenges and benefits that an organisation faces when it implements the integrated report or sustainability report and why sustainability is becoming a more important part of company reporting. Students will also analyse the similarities and differences between integrated reporting, traditional financial reporting and sustainability reporting.